Pesantren and Tolerance: Looking at the Faces of Santri Tolerance in Babakan Ciwaringin Cirebon - Hilyatul Auliya; H Syarif Abubakar; Noval Maliki (Jurnal Penelitian, 2019)
This study seeks to capture understanding of tolerance among santris in Babakan Islamic boarding school in Ciwaringin, Cirebon. Based on the findings of various research institutions which state that the Indonesian young generation turns out to have an alarming tolerance level, we try to target santris who have the same age range as respondents from PPIM Jakarta, for example. The method used in this study is quantitative descriptive with the help of SPSS 23.0 for windows as a calculation tool. The total population of santri in three schools is 4108, and the sample taken is 843 or about 20% of the population. The results of the study showed that understanding tolerance among santri in the Babakan Ciwaringin Cirebon boarding school was very high.